2014
DOI: 10.3402/tellusa.v66.23452
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm based on sea-level pressure fluctuations to identify major Baltic inflow events

Abstract: A B S T R A C T Major Baltic inflows are an important process to sustain the sensitive steady state of the Baltic Sea. We introduce an algorithm to identify atmospheric variability favourable for major Baltic inflows. The algorithm is based on sea-level pressure (SLP) fields as the only parameter. Characteristic SLP pattern fluctuations include a precursory phase of 30 days and 10 days of inflow period. The algorithm identifies successfully the majority of observed major Baltic inflows between 1961 and 2010. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 21 publications
1
32
2
6
Order By: Relevance
“…For these reasons we distance our analysis strategy from that taken by Matthäus (2006) or Schimanke et al (2014): instead of analyzing MBIs, or any salt inflow that reaches the lower layers of the Baltic Sea, as discrete or quantified phenomena, we perform our analysis on the resulting circulation which is directly driven by MBIs, that is the Baltic Sea haline conveyor belt as defined by Döös et al (2004). Döös et al (2004) define a meridional stream function in the Baltic Sea, which can be viewed along meridional and depth axis.…”
Section: Analysis Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…For these reasons we distance our analysis strategy from that taken by Matthäus (2006) or Schimanke et al (2014): instead of analyzing MBIs, or any salt inflow that reaches the lower layers of the Baltic Sea, as discrete or quantified phenomena, we perform our analysis on the resulting circulation which is directly driven by MBIs, that is the Baltic Sea haline conveyor belt as defined by Döös et al (2004). Döös et al (2004) define a meridional stream function in the Baltic Sea, which can be viewed along meridional and depth axis.…”
Section: Analysis Protocolmentioning
confidence: 99%
“…The work done by Schimanke et al (2014) identified atmospheric patterns related with MBIs. In their study, they used observed salinities following the protocol defined by Matthäus (2006) in order to identify MBIs.…”
Section: Analysis Protocolmentioning
confidence: 99%
See 3 more Smart Citations